Does Human Experimental Endotoxemia Impact Negative Cognitions Related to the Self? - Kotulla, Simone; Elsenbruch, Sigrid; Roderigo, Till; Brinkhoff, Alexandra; Wegner, Alexander; Engler, Harald; Schedlowski, Manfred; Benson, Sven (Frontiers in Behavioral Neuroscience, 2018)
A role of inflammatory processes in the pathophysiology of depression is increasingly recognized. Experimental endotoxemia offers an established model to induce transient systemic inflammation in healthy humans, and has been proposed as an experimental paradigm of depression. Indeed, different symptoms of depression can be observed during experimental endotoxemia, including negative mood or dysthymia as key symptoms of depression. Hopelessness and low self-esteem constitute common cognitive symptoms in depression, but have not been specifically assessed during endotoxemia. Thus, we pooled data from healthy volunteers who received low-dose endotoxin (i.e., 0.4 or 0.8 ng/kg lipopolysaccharide, LPS) or placebo in three randomized, controlled studies to investigate the effects of LPS on cognitive schemata related to depression. Validated questionnaires were used to assess self-esteem, hopelessness, and the vulnerability factor intolerance of uncertainty after intravenous injection of LPS or placebo. Plasma tumor necrosis factor (TNF)-α and interleukin (IL)-6 were repeatedly assessed, along with self-reported mood. Because not all questionnaires were available from primary studies, data were analyzed in two separate data sets: In data set 1, self-esteem and intolerance of uncertainty were assessed in N=87 healthy volunteers, who randomly received either 0.4 or 0.8 ng/kg LPS or placebo. In data set 2, hopelessness was measured in N=59 volunteers who randomly received either LPS (0.8 ng/kg) or placebo. In both data sets, LPS-application led to significant increases in TNF-α and IL-6, reflecting systemic inflammation. Positive mood was significantly decreased in response to LPS, in line with inflammation-induced mood impairment. General self-esteem, intolerance of uncertainty, and hopelessness did not differ between LPS- and placebo groups, suggesting that these negative cognitive schemata are not responsive to acute LPS-induced systemic inflammation. Interestingly, LPS-treated volunteers reported significantly lower body-related self-esteem, which was associated with increased TNF-α concentration. Thus, certain aspects of self-esteem related to physical attractiveness and sportiness were reduced. It is conceivable that this effect is primarily related to physical sickness symptoms and reduced physical ability during experimental endotoxemia. With respect to cognitive symptoms of depression, it is conceivable that LPS affects cognitive processes, but not negative cognitive schemata, which are rather based on learning and repeated experiences.